Distinct distribution of HEV-3 subtypes across humans, animals, and environmental waters in Sweden - Hao Wang; Marianela Patzi Churqui; Samaneh Taslimi; Timur Tunovic; Linn Dahlsten Andius; Martin Lagging; Kristina Nyström (Emerging Microbes and Infections)
We previously observed a notable discrepancy in the distribution of HEV-3 subtypes between wastewater and clinical samples in Sweden. To confirm this observation and comprehensively elucidate HEV-3 circulation patterns across humans, animals, and environmental waters in Sweden, we analysed the HEV genetic diversity in archived wastewater samples between late 2016 and early 2018, clinical cases between 2012 and 2024, and all available Swedish sequences from the NCBI Virus database. HEV RNA was detected in all archived wastewater samples, with subtype 3c being the only subtype identified. In typed clinical cases, subtypes 3f (45/126) and 3c (44/126) were nearly equally distributed, though regional dominance varied. When incorporating human sequences from other Swedish studies, subtype 3f became dominant (75/168). Analysis of all available sequences revealed that 3f (113/136) was the dominant subtype in Sus scrofa (pigs and wild boars), while 3c (30/33) was dominant in environmental waters. These findings highlight the complex transmission dynamics of HEV-3 in Sweden. The near-absence of 3c in Swedish domestic pigs and wild boars, despite its high proportion in clinical cases, raises the question about the source of human 3c infection. In addition, the near-exclusive detection of 3c in wastewater suggests potential differences in viral shedding, disease severity of HEV-3 subtypes, or alternative host sources. This study emphasizes the importance of integrated One Health surveillance to track HEV circulation across reservoirs.